An Admission Test for Intermediate Accounting. - Delaney, Patrick R.; Keys, David E.; Norton, Curtis L.; Simon, John R. (The Accounting Review, 1979)
ABSTRACT: This article describes the results obtained when an admission test was developed and used at Northern Illinois University as an accept-reject device for our first intermediate accounting course. The results indicate that it is possible to develop an admission test, that the test need not be lengthy, and that acceptable levels of correlation exist between the admission test scores and success or failure in the first intermediate accounting course.